#### 2.132   ODE No. 132

$3 x y'(x)-y(x)-3 x y(x)^4 \log (x)=0$ Mathematica : cpu = 0.0797806 (sec), leaf count = 115

$\left \{\left \{y(x)\to \frac {(-2)^{2/3} \sqrt [3]{x}}{\sqrt [3]{3 x^2-6 x^2 \log (x)+4 c_1}}\right \},\left \{y(x)\to \frac {2^{2/3} \sqrt [3]{x}}{\sqrt [3]{3 x^2-6 x^2 \log (x)+4 c_1}}\right \},\left \{y(x)\to -\frac {\sqrt [3]{-1} 2^{2/3} \sqrt [3]{x}}{\sqrt [3]{3 x^2-6 x^2 \log (x)+4 c_1}}\right \}\right \}$ Maple : cpu = 0.03 (sec), leaf count = 153

$\left \{ y \left ( x \right ) ={\frac {1}{6\,{x}^{2}\ln \left ( x \right ) -3\,{x}^{2}-4\,{\it \_C1}}\sqrt [3]{-4\,x \left ( 6\,{x}^{2}\ln \left ( x \right ) -3\,{x}^{2}-4\,{\it \_C1} \right ) ^{2}}},y \left ( x \right ) ={\frac {i\sqrt {3}-1}{12\,{x}^{2}\ln \left ( x \right ) -6\,{x}^{2}-8\,{\it \_C1}}\sqrt [3]{-4\,x \left ( 6\,{x}^{2}\ln \left ( x \right ) -3\,{x}^{2}-4\,{\it \_C1} \right ) ^{2}}},y \left ( x \right ) =-{\frac {1+i\sqrt {3}}{12\,{x}^{2}\ln \left ( x \right ) -6\,{x}^{2}-8\,{\it \_C1}}\sqrt [3]{-4\,x \left ( 6\,{x}^{2}\ln \left ( x \right ) -3\,{x}^{2}-4\,{\it \_C1} \right ) ^{2}}} \right \}$